2000
DOI: 10.1128/jb.182.5.1442-1447.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c ′ from Rhodobacter capsulatus Confers Increased Resistance to Nitric Oxide

Abstract: We report the cloning and sequencing of the gene containing cytochrome c′ (cycP) from the photosynthetic purple bacterium Rhodobacter capsulatus and the regions flanking that gene. Mutant strains unable to synthesize cytochromec′ had increased sensitivity to nitrosothiols and to nitric oxide (which binds to the heme moiety of cytochrome c′).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 31 publications
4
56
0
Order By: Relevance
“…This finding led to the suggestion that Cyt cЈ is involved in minimizing NO damage during denitrification. More recent results from studies with Rhodobacter capsulatus are consistent with the proposal that Cyt cЈ protects against NO damage (8,9). Mutations in cycP, which encodes Cyt cЈ, increased the sensitivity to both S-nitrosoglutathione (GSNO) and free NO (8).…”
supporting
confidence: 73%
“…This finding led to the suggestion that Cyt cЈ is involved in minimizing NO damage during denitrification. More recent results from studies with Rhodobacter capsulatus are consistent with the proposal that Cyt cЈ protects against NO damage (8,9). Mutations in cycP, which encodes Cyt cЈ, increased the sensitivity to both S-nitrosoglutathione (GSNO) and free NO (8).…”
supporting
confidence: 73%
“…Despite their ubiquity in bacteria, the biological role of cytochromes c¢ remains unclear. Although a role in electron transfer processes had been assumed for a long time [7], more recently it has been suggested that cytochromes c¢ are involved in protection against high levels of NO [8,9]. Scientific interest in cytochromes c¢ has increased further owing to the similarities in spectral properties and ligand binding properties between cytochrome c¢ from Alcaligenes xylosoxidans and sGC [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In some bacteria heme sensors were recently discovered (5) with a femtomolar affinity for NO, whereas cytochromes cЈ able to bind NO are found in many nitrogen-fixing, denitrifying, and photosynthetic bacteria (6). Although the physiological role the bacterial cytochrome cЈ from Alcaligenes xylosoxidans (AXCP) 2 is not yet established, the homologous cytochrome cЈ from Rhodobacter capsulatus has been shown to increase the resistance of this bacteria against NO toxicity (7,8). Thus, the bacterial cytochromes cЈ are inferred to disclose a particular behavior regarding NO dynamics and affinity.…”
mentioning
confidence: 99%
“…Recent studies have shown that cytochrome cЈ from R. capsulatus (RCCP) helps protect this organism against NO toxicity (7,8). Specifically, the resistance of the bacteria to NO is increased when RCCP is expressed, but buffering alone cannot account for this effect (8).…”
mentioning
confidence: 99%